2013
DOI: 10.1371/journal.pone.0084151
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Flux Distribution within Streptomyces coelicolor Metabolism: A Comparison between the Actinorhodin-Producing Strain M145 and Its Non-Producing Derivative M1146

Abstract: Metabolic Flux Analysis is now viewed as essential to elucidate the metabolic pattern of cells and to design appropriate genetic engineering strategies to improve strain performance and production processes. Here, we investigated carbon flux distribution in two Streptomyces coelicolor A3 (2) strains: the wild type M145 and its derivative mutant M1146, in which gene clusters encoding the four main antibiotic biosynthetic pathways were deleted. Metabolic Flux Analysis and 13C-labeling allowed us to reconstruct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 118 publications
(139 reference statements)
6
35
0
Order By: Relevance
“…Meanwhile, nucleoside triphosphate levels strongly regulate ribosomal RNA synthesis, and we therefore hypothesize that a higher ATP/ADP ratio in M1152 compared to M145 after phosphate depletion may be causing the differences in expression of ribosomal proteins. The observed upregulation of the ATP-synthase gene cluster supports this hypothesis (Figure S9A), and a high level of ATP has been reported in the M1146 strain parental to M1152 (Coze et al, 2013b) which also lacks the 4 major BGCs but does not feature the rpoB mutation. Regardless, neither of these hypotheses can explain why a difference in ribosomal protein expression is only seen in production phase, and the correlation with the metabolic switch indicates that it may as well be related to the lack of the four BGCs or the produced compounds.…”
Section: Elevated Expression Of Ribosomal Proteins In M1152 After Phosupporting
confidence: 79%
See 2 more Smart Citations
“…Meanwhile, nucleoside triphosphate levels strongly regulate ribosomal RNA synthesis, and we therefore hypothesize that a higher ATP/ADP ratio in M1152 compared to M145 after phosphate depletion may be causing the differences in expression of ribosomal proteins. The observed upregulation of the ATP-synthase gene cluster supports this hypothesis (Figure S9A), and a high level of ATP has been reported in the M1146 strain parental to M1152 (Coze et al, 2013b) which also lacks the 4 major BGCs but does not feature the rpoB mutation. Regardless, neither of these hypotheses can explain why a difference in ribosomal protein expression is only seen in production phase, and the correlation with the metabolic switch indicates that it may as well be related to the lack of the four BGCs or the produced compounds.…”
Section: Elevated Expression Of Ribosomal Proteins In M1152 After Phosupporting
confidence: 79%
“…Meanwhile, simulations with EcSco-GEM reveal that more than half of the glutamate-derived nitrogen is excreted as ammonia into the medium ( Figure S6B). A reduced flux through glycolysis has previously been reported for strain M1146 lacking the four BGCs, and it is suggested that this is caused by allosteric inhibition of phosphofructokinase by a higher ATP/ADP ratio in the M1146 strain (Coze et al, 2013a;Esnault et al, 2017).…”
Section: M1152 and M145 Differ Significantly In Central Carbon Metabomentioning
confidence: 66%
See 1 more Smart Citation
“…Intracellular and extracellular actinorhodin contents were quantified following the protocol (56) with a single modification using 1 m NaOH instead of 1 m KOH. Intracellular actinorhodin content was quantified from 1-ml culture pellet, whereas supernatant was used to quantify the extracellular γ-actinorhodin.…”
Section: Methodsmentioning
confidence: 99%
“…Lignocellulosic substrates (1.2 g) were sterilized with 19 ml of water in 150-ml growth flasks, and 1 ml of minimal medium without glucose. (Coze et al, 2013) was added to obtain a final volume of 20 ml. Inoculations were done with 3 × 10 8 spores per flask.…”
Section: Strains Media and Culture Conditionsmentioning
confidence: 99%